2017
DOI: 10.1007/s00266-017-0841-z
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Alopecia with Localized Scalp Necrosis After Accidental Embolization of the Parietal Artery with Hyaluronic Acid

Abstract: Hyaluronic acid (HA) filler injection is widely used for soft-tissue augmentation. Complications associated with HA filling are not uncommon; however, HA-induced alopecia is a rarely reported complication that could result in severe secondary psychological trauma. The etiology, clinical traits, treatment strategies, outcomes, and possible reversibility of HA-induced alopecia have not been characterized. Here, we report a case in which bilateral temple injections of 6.5 mL of HA led to persistent pain over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…4 It was suggested that the mutations on the N and C terminals of LSS may result in hypotrichosis and congenital cataract, respectively. 3 However, the patients in our family who harbored…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…4 It was suggested that the mutations on the N and C terminals of LSS may result in hypotrichosis and congenital cataract, respectively. 3 However, the patients in our family who harbored…”
mentioning
confidence: 82%
“…Since the first report of FIA by Gan et al in 2013, 2 there have only been three cases to date. [2][3][4] All cases were of women. Two of these cases were ipsilateral on the temporal scalp after HA filler injection, and one case was on the forehead after calcium hydroxyapatite filler.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the clinical diseases that can be categorized in this form are known as "Late-stage nonscarring alopecias" including alopecia areata, patterned hair loss, and traction alopecia, etc. Recent report indicated that the occurrence of biphasic alopecia can also be iatrogenic [13].…”
Section: Pathology Of Cicatricial Alopeciamentioning
confidence: 99%
“…Mechanistically, Figure 6. Hyaluronic acid filling in the left temple region results in the skin necrotic and ischemic lesion leading to an area of a permanent hair loss surrounded by regions with slow-restoration of hair regrowth [13]. (a) Complete hair loss was seen in the patient's left temple area after HA injection.…”
Section: The Application Of Minoxidilmentioning
confidence: 99%